Pengaruh Injeksi Platelet Rich Plasma Terhadap Proses Penyembuhan Luka Fase Remodeling Berdasarkan Early Wound Healing Score (EHS) pada Kasus Sistokel - Betrisya Hanifah; Jojor Sihotang (Fakultas Kedokteran Universitas Riau, 2026)
Pelvic organ prolapse (POP) is a common condition in postpartum women, with cystocele being the most common type. Anterior colporrhaphy is a commonly used treatment, but it has a relatively high recurrence rate. Platelet-rich plasma (PRP) is known to have the potential to enhance wound healing through tissue regeneration. This study aims to analyze the effect of PRP injection on remodeling phase wound healing based on the Early Wound Healing Score (EHS) assessment in cystocele cases. The study design used was a retrospective cohort, with data taken from medical records using a consecutive sampling method on 40 women who underwent anterior colporrhaphy. A total of 20 patients who received PRP injection were included in the case group, while 20 other patients who did not receive PRP injection were the control group. The EHS score was assessed on the 14th and 28th days postoperatively. Data analysis was performed using the independent t-test on day 14 and the Mann-Whitney test on day 28. The results showed a significant increase in the mean EHS score in the case group compared to the control group, both on day 14 and day 28. In conclusion, PRP injection during cystocele surgery has been proven effective in accelerating wound healing in the remodeling phase and has the potential to be an additional therapy to reduce the risk of recurrence.